To simplify the expression (p-3)-(2.4+2p), we can distribute the negative sign to the terms inside the parentheses.
First, we distribute the negative sign to (2.4+2p):
-(2.4+2p) = -2.4 - 2p
Now, we rewrite the expression using the distributed forms:
(p - 3) - (2.4 + 2p) = p - 3 - 2.4 - 2p
Next, we group similar variables together:
(p - 2p) - (3 + 2.4) = -p - 2.4 - 3
Finally, we combine like terms:
-p - 2.4 - 3 = -p - 5.4
Therefore, the simplified expression is -p - 5.4.
Use the properties of operations to subtract (p-3)-(2.4+2p)
1 answer